Gender equality in education: challenges for boys in choosing care professions - Pilinkaitė - Sotirovič, Vilana (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] This article analyzes how gender equality discourses shape the opportunities for boys to choose non-traditional professions in the care economy (kindergarten teachers, teachers in the elementary schools, social workers, nurses etc.). Research on gender equality in education examines the paths for girls in physical and technological sciences (STEM) and highlights the impact of gender stereotypes and the traditional perceptions of gender roles on women in choosing careers in this field. As some comparative research in the EU has shown, numbers of women in “male-dominated” professions increased in the last two decades. Nevertheless, the men’s move to care professions is very slow due to the lack of support for boys to choose non-traditional/atypical professions (Scambor et al. 2013). By applying discourse analysis, this article examines the content (texts and visuals) of the methodological material for vocational counseling (www.mukis.lt). It suggests that a gender-neutral and gender-differentiated conceptualization of profession preferences, motivation and representation are present in the content of vocational material, while the gender-pluralistic approach tends to be absent. Care professions in general are almost invisible in the content of vocational training materials (the silence discourse) and represented only by women. These tendencies suggest the reproduction of gendered norms and understandings about different gender roles in society. The discourse regarding men’s engagement in care professions is still underdeveloped in Lithuania.